Acculturation Strategy and Racial Group in the Perception of Immigrants. (13th March 2017) - Alcott, Yvette D.; Watt, Susan E.
We investigated the effects of race and different acculturation strategies on perceptions of immigrants in Australia, an immigrant-based nation with a multicultural policy. Two experimental studies presented participants with scenarios that systematically varied racial group (African, Asian, and European) and acculturation strategy (assimilation, integration, separation, marginalisation), then assessed responses to immigrant targets using measures of warmth, competence, affect, and cultural distance. Attitudes were significantly more positive towards targets who either integrated or assimilated, and negative towards targets who separated. This was regardless of the racial group being assessed, supporting the prediction that acculturation strategy is a stronger influence than race on perceptions of immigrants.